Determination of conductivity in a heat equation - Ping Wang; Kewang Zheng (International Journal of Mathematics and Mathematical Sciences)
We consider the problem of determining the conductivity in a heat equation from overspecified non-smooth data. It is an ill-posed inverse problem. We apply a regularization approach to define and construct a stable approximate solution. We also conduct numerical simulation to demonstrate the accuracy of our approximation.